Crystalline phases in nylon-11: studies using HTWAXS and HTFTIR - Nair, S. S.; Ramesh, C.; Tashiro, K. (Macromolecules, 2006)
Nylon-11 was crystallized into different crystalline phases by appropriate methods. The chance in the structure during heating was monitored in situ by wide-angle X-ray scattering (WAXS). The alpha phase obtained by precipitating nylon-11 in 1,4-butanediol started transforming into the pseudohexagonal phase on heating, but the transformation was not fully completed before melting. The melt crystallized sample at 175 degrees C gave the pseudohexagonal phase, which transformed into the alpha' phase on cooling to room temperature at about 100 degrees C. The d spacing of the 00 1 reflection also showed a change at the transition temperature. The melt-quenched sample showed the pseudohexagonal phase, which did not change during heating, but on cooling transformed into alpha' phase. The gamma phase was obtained by casting nylon-11 in trifluoroacetic acid (TFA), and it changed into the pscudohexagonal phase at about 110 degrees C on heating. The d spacing of the 001 reflection depended on the way in which it was obtained. The studies have shown that nylon-11 is one of the few nylons that exhibit an extensive degree of polymorphism. High-temperature Fourier transform infrared spectroscopy (HTFTIR) studies revealed, apart from the conformational differences between various phases of nylon-11, some information on the formation of the gamma phase.

Copolyesters based on poly(butylene terephthalate)s containing cyclohexyl and cyclopentyl ring: Effect of molecular structure on thermal and crystallization behavior - Sandhya, T. E.; Ramesh, C.; Sivaram, S. (Macromolecules, 2007)
In an effort to understand the role of molecular structure on the thermal properties of polyesters and copolyesters, the following polyesters were synthesized: poly(1,4-cyclohexane dimethylene terephthalate) (PCT), poly(butylene-1,4-cyclohexane dicarboxylate) (PBCD), poly (1,3-cyclopentane dimethylene terephthalate) (PCPDT), and poly(butylene-1,3-cyclopentane dicarboxylate) (PBCP). PCT and PCPDT are semicrystalline polymers with crystallization and melting temperatures higher than poly(butylene terephthalate) (PBT). However, PBCD and PBCP have lower glass transition temperature than PBT. From these homopolymers a series of poly(butylene-co-1,4-cyclohexane dimethylene terephthalate) (P(BT-co-CT )), poly(butylene terephthalate-co-1,4cyclohexane dicarboxylate) (P(BT-co-BCD)), poly(butylene-co-1,3-cyclopentylene dimethylene) (P(BT-co-CPDT)), and poly(butylene terephthalate-co-1,3-cyclopentane dicarboyxlate) (P(BT-co-PBCP)) random copolyesters were synthesized for the first time, and their cocrystallization behavior was investigated using differential scanning calorimetry (DSC) and wide-angle X-ray diffraction (WAXD). The copolymers were found to be statistically random and crystallized in all compositions. The P(BT-co-CT) and (P(BT-co-CPDT) copolyesters exhibited typical eutectic behavior in melting and crystallization, which indicated isodimorphic cocrystallization behavior. On the other hand, in the case of P(BT-co-BCD) and P(BT-co-PBCP) copolymers, the melting and crystallization temperatures showed linear dependency with composition, indicating isomorphic-like crystallization behavior.